2021
DOI: 10.1164/rccm.202103-0814oc
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Upper Respiratory Tract Microbiota and Its Association with Mortality in COVID-19

Abstract: Impact: This study demonstrates the association between the upper respiratory tract microbiota and the prognosis in COVID-19. A higher abundance of Streptococcus on admission predicts a lower mortality rate. The upper respiratory tract microbiota may reflect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
76
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 49 publications
11
76
1
Order By: Relevance
“…The available evidence suggests a potential role of microbiota in susceptibility to SARS-CoV-2 infection and COVID-19 severity, but longitudinal studies evaluating the microbiota as a prognostic factor for severity of disease progression are lacking [19] , [20] , [21] , [22] . The data regarding the association between nasopharyngeal microbiota features and disease severity are scarce and limited in terms of showing a decrease in α diversity or identifying specific genera with relevance to critical illness [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The available evidence suggests a potential role of microbiota in susceptibility to SARS-CoV-2 infection and COVID-19 severity, but longitudinal studies evaluating the microbiota as a prognostic factor for severity of disease progression are lacking [19] , [20] , [21] , [22] . The data regarding the association between nasopharyngeal microbiota features and disease severity are scarce and limited in terms of showing a decrease in α diversity or identifying specific genera with relevance to critical illness [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies focused on microbiota factors that were associated with COVID-19 severity and outcomes. For example, Mycoplasma salivarium enrichment in the lung microbiota was described as a marker for disease severity and Streptococcus abundance in the oropharyngeal microbiota was indicated as a marker for survival until discharge [25,26]. However, as Lloréns-Rico and colleagues demonstrate in their analysis based on 58 upper and 35 lower respiratory tract microbiota samples from well defined COVID-19 patients, intensive care stay including antibiotic courses and mechanical ventilation strongly confounds microbiota composition changes attributed to SARS-CoV-2 infection, hampering interpretation of results found in severely ill COVID-19 patients [27 ▪ ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies focused on microbiota factors that were associated with COVID-19 severity and outcomes. For example, Mycoplasma salivarium enrichment in the lung microbiota was described as a marker for disease severity and Streptococcus abundance in the oropharyngeal microbiota was indicated as a marker for survival until discharge [25,26] ]. To gain more insight in the role of the respiratory microbiota during SARS-CoV-2 infection, large-scale prospective studies in an area with high SARS-CoV-2 transmission rates are needed.…”
Section: Key Pointsmentioning
confidence: 99%
“…A study analyzing oropharyngeal, nasopharyngeal, and endotracheal samples from hospitalized COVID-19 patients using 16S rRNA sequencing reported respiratory tract bacterial dysbiosis in patients with COVID-19; microbial signatures were also associated with COVID-19 severity and systemic immune response (12). Recent studies have also reported lower airway microbial signatures associated with poor clinical outcome of COVID-19 and upper respiratory microbiota associated with mortality and COVID-19 severity (18,19). These early findings suggest that the airway microbiome may be an important factor in indicating and influencing COVID-19 clinical outcomes and should be investigated further.…”
Section: Introductionmentioning
confidence: 99%